Evaluasi Program Kerja Mahasiswa Kampus Mengajar dengan Metode Goal Oriented - Ramadhani, Adila Destri; Trimurtini, Trimurtini; Purwati, Panca Dewi (Smart Education, 2023)
Abstract: This study aims to describe the evaluation of the Kampus Merdeka program using the Tyler program evaluation method: goal oriented. The research methods used are quantitative and qualitative, with a descriptive research design. The research was conducted at SD Negeri Banyumeneng 02 Demak Regency. The data collection technique was completed by filling out questionnaires, interviews, and documentation by resource persons, namely guest teachers, principals, and field supervisors (DPL). The results of the study showed that the results of questionnaires and interviews with sources at the time of formulation, when implemented, and reports on the implementation of the Teaching Campus class 2 student work program in terms of cultural aspects, curriculum aspects, and aspects of technology adaptation in learning obtained a significant increase from the three aspects of the study. The results showed that the suitability of the Teaching Campus class 2 student work program with the objectives of the Teaching Campus class 2 program was 87.547%. Based on the methods and stages of Tyler W.'s goal-oriented evaluation, the evaluation of the Teaching Campus class 2 student work program is based on the objectives of the Teaching Campus program. The implementation of the work program is guided by the program's objectives, producing outputs beneficial to schools and students so that the Teaching Campus program activities are worth continuing.Keywords: evaluation; Kampus Mengajar; work program.Abstrak: Penelitian ini bertujuan mendeskripsikan evaluasi program Kampus Merdeka dengan metode evaluasi program Tyler: Goal Oriented. Metode penelitian yang digunakan adalah kuantitatif dan kualitatif dengan desain penelitian deskriptif. Penelitian dilakukan di SD Negeri Banyumeneng 02 Kabupaten Demak. Teknik pengumpulan data dilakukan dengan pengisian angket, wawancara, dan dokumentasi yang diisi oleh narasumber yakni guru pamong, kepala sekolah, dan dosen pembimbing lapangan (DPL). Hasil penelitian diketahui hasil angket dan wawancara narasumber pada saat perumusan, saat dilaksanakan, dan laporan pelaksanaan program kerja mahasiswa Kampus Mengajar angkatan 2 dalam segi aspek budaya, aspek kurikulum, dan aspek adaptasi teknologi dalam pembelajaran didapat kenaikan yang signifikan dari ketiga aspek penelitian. Hasil penelitian menunjukkan kesesuaian program kerja mahasiswa Kampus Mengajar angkatan 2 dengan tujuan program Kampus Mengajar angkatan 2 memperoleh 87,547%. Berdasarkan metode dan tahapan evaluasi goal-oriented Tyler W. dalam evaluasi program kerja mahasiswa Kampus Mengajar angkatan 2 sangat sesuai dengan tujuan program Kampus Mengajar. Penerapan program kerja yang sesuai dengan tujuan program, menghasilkan out put yang bermanfaat bagi sekolah dan juga peserta didik sehingga kegiatan program Kampus Mengajar layak diteruskan.Kata kunci: evaluasi; Kampus Mengajar; program Kerja